Handshape complexity as a precursor to phonology: Variation, Emergence, and Acquisition - Brentari, Diane (Lang Acquis, 2016)
In this paper two dimensions of handshape complexity are analyzed as potential building blocks of phonological contrast—joint complexity and finger group complexity. We ask whether sign language patterns are elaborations of those seen in the gestures produced by hearing people without speech (pantomime) or a more radical re-organization of them. Data from adults and children are analyzed to address issues of cross-linguistic variation, emergence, and acquisition. Study 1 addresses these issues in adult signers and gesturers from the United States, Italy, China, and Nicaragua. Study 2 addresses these issues in child and adult groups (signers and gesturers) from the United States, Italy, and Nicaragua. We argue that handshape undergoes a fairly radical reorganization, including loss and reorganization of iconicity and feature redistribution, as phonologization takes place in both of these dimensions. Moreover, while the patterns investigated here are not evidence of duality of patterning, we conclude that they are indeed phonological, and that they appear earlier than related morphosyntactic patterns that use the same types of handshape.